An Assessment of the Impact of Funding Gap on Financial Perfomance of Parastatals - Makurumidze, Clive K (Midlands State University, 2017)
The research focused on the impact of funding gap on profitably of SMEDCO, thus how the lack of working capital has affected the financial performance of the corporation. The research was inspired by the failure of the corporation to fulfil its mandate of giving loans to small and medium enterprises due to lack of funds. SMEDCO has put a moratorium on disbursements as the corporation has no funds for disbursements. This has affected the financial performance of the corporation as SMEDCO has been recording losses since the inception of USD era. Literature related to the study was also reviewed so as to fortify the base of the research. The research incorporated a mixed approach so as to cater for both qualitative and quantitative data. Descriptive, correlation research approaches with a sample size of 31 respondents was exploited in collecting primary and secondary data. The author also used questionnaires and interviews as instruments to collect data. Tables, graphs and charts were used in presenting and analysing the data collected. The research proved that the funding gap that has affected SMEDCO arose from failure to attain external funding due to lack of collateral security and political instability. The research suggested that SMEDCO should engage financial institutions so as to get funding. It was recommended that the corporation can downsize or use debt factoring so as to improve its working capital level.